2017
DOI: 10.1016/j.jmbbm.2017.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical response of human female breast skin under uniaxial stretching

Abstract: Skin is a complex material covering the entire surface of the human body. Studying the mechanical properties of skin to calibrate a constitutive model is of great importance to many applications such as plastic or cosmetic surgery and treatment of skin-based diseases like decubitus ulcers. The main objective of the present study was to identify and calibrate an appropriate material constitutive model for skin and establish certain universal properties that are independent of patient-specific variability. We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…Several of these models treat the skin as an isotropic elastic material with a nonlinear response. Although, some of these models were capable of predicting the stiffening effect observed in experiments, they fail to represent the anisotropic behavior widely observed in experiments (Evans and Holt, 2009;Flynn et al, 2011b;Hendriks et al, 2006;Kumaraswamy et al, 2017). In previous work, our group examined the mechanical properties of female breast skin, but under uniaxial loading conditions (Kumaraswamy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several of these models treat the skin as an isotropic elastic material with a nonlinear response. Although, some of these models were capable of predicting the stiffening effect observed in experiments, they fail to represent the anisotropic behavior widely observed in experiments (Evans and Holt, 2009;Flynn et al, 2011b;Hendriks et al, 2006;Kumaraswamy et al, 2017). In previous work, our group examined the mechanical properties of female breast skin, but under uniaxial loading conditions (Kumaraswamy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical properties of skin have been studied by a number of authors [see for example, porcine: (Khatam and Ravi-Chandar, 2013;Shergold et al, 2006); murine: (Muñoz et al, 2008); human: (Agache et al, 1980;Bischoff et al, 2000;Clark et al, 1996;Dunn and Silver, 1983;Hendriks et al, 2003;Kumaraswamy et al, 2017;Kvistedal and Nielsen, 2009;Reihsner and Menzel, 1996;Silver et al, 2001;Tonge et al, 2013aTonge et al, , 2013c; Wan Abas and Barbenel, 1982;Ní Annaidh et al, 2012b, 2012a; and rabbit Fung, 1974a, 1974b)]. These studies were motivated by different objectives such as understanding the mechanics of stabbing (McCarthy et al, 2010(McCarthy et al, , 2007, planning plastic surgery, dermatology, impact biomechanics (Gallagher et al, 2012;Ní Annaidh et al, 2012a), and designing devices that interact with the skin, such as shaving blades (Evans et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 26 It is this collagen failure (occurring due to defibrillation) that signifies skin damage. 27 In healthy breast skin samples, Kumaraswamy et al 28 identified up to 58% strain without fibril damage. However, strain assessment was performed in vitro using a testing rig restricted to 58% strain.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy breast skin samples, Kumaraswamy et al 28 identified up to 58% strain without fibril damage. However, strain assessment was performed in vitro using a testing rig restricted to 58% strain.…”
Section: Introductionmentioning
confidence: 99%